Artistic Creation at the “Studio” Theater of the University of Arts Târgu Mureș, in the Period 1979-2001 - Florea, Magdalena (Theatrical Research, 2022)
The present study aimed to present in a dynamic evolution the reception of the artistic creation of the “Studio” Theater of the University of Arts in Târgu Mureș. For this analysis, the statistical data of the Faculty of Arts in Romanian was used regarding the reception of the shows per academic year, in the period 1979-2001. The following indicators were used to measure the audience: the number of shows per season, per show and total shows produced and presented; the number of spectators per season and per show; the average number of spectators per show.